Steady‐State Ceftazidime‐Avibactam Serum Concentrations and Dosing Recommendations in a Critically Ill Patient Being Treated for Pseudomonas aeruginosa Pneumonia and Undergoing Continuous Venovenous Hemodiafiltration. Issue 12 (31st October 2019) - Soukup, Paige; Faust, Andrew C.; Edpuganti, Vindhya; Putnam, William C.; McKinnell, James A.
Abstract : Ceftazidime‐avibactam (CAZ‐AVI) is a novel intravenous β‐lactam/β‐lactamase inhibitor combination used in the treatment of multidrug‐resistant (MDR) gram‐negative infections. Although renal dosing recommendations exist for the medication, limited data are available for dosing in patients receiving continuous renal replacement therapy. In this report, we describe a case in which CAZ‐AVI 2.5 g was administered as a 2‐hour infusion every 8 hours to a 50‐year‐old critically ill patient with MDR Pseudomonas aeruginosa (CAZ‐AVI minimum inhibitory concentration [MIC] 8 μg/ml) pneumonia who was also receiving continuous venovenous hemodiafiltration (CVVHDF). Total serum concentrations of both ceftazidime and avibactam were measured at 0.5, 2, 4, and 6 hours after completion of the 2‐hour infusion of the 11th dose of CAZ‐AVI. Ceftazidime pharmacokinetic parameters were as follows: maximum serum concentration (Cmax ) 152.39 μg/ml, half‐life 5.17 hours, volume of distribution at steady state (Vdss ) 11.51 L, clearance 1.54 L/hour, and area under the concentration‐time curve (AUC) 1295.38 hourμg/ml. This regimen achieved free ceftazidime serum concentrations more than 4 times the MIC for 100% of the dosing interval. Avibactam pharmacokinetic parameters were as follows: Cmax 35.83 μg/ml, half‐life 5.92 hours, Vdss 12.44 L, clearance 1.45 L/hour, and AUC 343.44 hourμg/ml, which achieved free avibactam concentrations above 1 μg/ml for 100% of the dosing interval. Higher CAZ‐AVI dosing is critical in the treatment of pneumonia due to limited ceftazidime penetration into epithelial lining fluid; however, epithelial lining fluid drug concentrations were not collected or measured. Based on this case report and the available evidence, a dose of CAZ‐AVI 2.5 g infused over 2 hours every 8 hours appears to be appropriate for critically ill patients who are being treated for pneumonia and are receiving CVVHDF.